Kelayakan Sediaan Kosmetik Pewarna Rambut dari Ekstrak Daun Pacar Kuku (Lowsonia Inermis) Sebagai Sediaan Kosmetik Pewarna Rambut Beruban - Hilmi Habibah; Febri Silvia; Siti Hajar Thaitami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Hair is a part of the body that requires care, one of which is thorugh the use of hair dye. To obtain safer alternative, natural hair dye was developed from henna leaf extract (Lawsonia inermis). This study aims to analyze the formulation of hair dye cosmetic from henna leaf extract through laboratory tests (lawsone content, tannin content, and pH), organoleptic tests (texture, color, aroma), and hedonic tests (panelist preference). The reseacrh employed an experimental quantitative approach involving 7 panelists consisting of 2 lecturers in beauty and makeup, 2 pharmacists, and 3 beauty students. Data were collected through observation, documentation, and questionnaires. The result showed that all formulations (F1, F2, F3) tested positive for lawsone and tannin content and had a pH value of 5, which meets the standard pH for hair dye. In the organoleptic test, formulation F2 was rated the best, with 86% of panelists stating the texture was thick, 57% stating the color was deep yellow, and 72% stating the aroma was characteristic of henna leaf extract. In the hedonic test, formulation F1 was fairly liked (86%) and formulation F3 was liked by 86% of the panelists. Based on these results, hair dye cosmetics made from henna leaf extract are considered suitable for use as natural hair dye products.